2020
DOI: 10.3390/cancers12020335
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Photodynamic Detection of Adult T-cell Leukemia/Lymphoma and Specific Leukemic Cell Death Induced by Photodynamic Therapy: Current Status in Hematopoietic Malignancies

Abstract: Adult T-cell leukemia/lymphoma (ATL), an aggressive type of T-cell malignancy, is caused by the human T-cell leukemia virus type I (HTLV-1) infections. The outcomes, following therapeutic interventions for ATL, have not been satisfactory. Photodynamic therapy (PDT) exerts selective cytotoxic activity against malignant cells, as it is considered a minimally invasive therapeutic procedure. In PDT, photosensitizing agent administration is followed by irradiation at an absorbance wavelength of the sensitizer in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…The CD47 agonist peptide PKHB1, hyaluronic acid nanoparticles, Withania somnifera, and photodynamic therapy can all be used to induce ICD in lymphocytic leukemia cells. [154][155][156][157] But, more efficient ICD inducers need to be explored.…”
Section: Lymphocytic Leukemiamentioning
confidence: 99%
“…The CD47 agonist peptide PKHB1, hyaluronic acid nanoparticles, Withania somnifera, and photodynamic therapy can all be used to induce ICD in lymphocytic leukemia cells. [154][155][156][157] But, more efficient ICD inducers need to be explored.…”
Section: Lymphocytic Leukemiamentioning
confidence: 99%
“…Sensitive Photodynamic Detection of Adult T-cell Leukemia/Lymphoma and Specific Leukemic Cell Death Induced by Photodynamic Therapy: Current Status in Hematopoietic Malignancies: Oka et al demonstrated in this article that ALA-PDT is very effective in selectively eliminating in vitro Adult T-cell Leukemia/Lymphoma (ATL) cells while preserving the normal ones [ 11 ]. These findings support the use of orally administered 5-ALA, and then visible light exposure of ATL cells and normal lymphocytes in peripheral blood using the extracorporeal circulation system.…”
Section: Research Snippetsmentioning
confidence: 99%
“…Clinical anti-cancer applications of 5-ALA-PDT have been widely reported for several organs, such as the brain [ 11 , 12 , 13 , 14 , 15 , 16 ], skin [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], pharynx [ 24 ], blood and lymph [ 25 ], esophagus [ 26 ], urethra and prostate [ 27 ], and uterus [ 28 ]. In addition, 97 clinical trials of 5-ALA PDT for cancer treatment have been registered in the U.S. National Library of Medicine (ClinicalTrials.gov) as of 10 March 2021.…”
Section: Introductionmentioning
confidence: 99%